THE RELATIONSHIP BETWEEN MOTIVATION AND PERFORMANCE OF FAMILY PLANNING FIELD OFFICIALS IN THE CENTER OF THE UPT DEPARTMENT OF PPKB BANDAR DISTRICT SIMALUNGUN DISTRICT - Eka Sihombing (PT. Radja Intercontinental Publishing, 2020)
The Family Planning Field Officer (PLKB) is one of the Human Resources (HR) in carrying out family planning services at the Family Planning Center. KB Center is an important resource and much needed to achieve optimal performance. The success or failure of an organization engaged in family planning services such as a family planning center depends on the ability of Human Resources (HR) to carry out its activities. This type of research is a quantitative research that is analytic in nature using a cross-sectional design, namely the dependent variable and independent variable carried out at the same time. Data obtained through direct interviews with respondents using a check list sheet filled in by the respondent. Where the total population is 19 people. The results of the Chi-Sguare statistical test obtained p value = 0, 004≤ α (0.05). So that it is known that there is a relationship between motivation and leadership performance at the UPTD KB Hall, Bandar District, Simalungun Regency. The results of the Chi-Sguare statistical test obtained p value = 0.014≤α (0.05). So that it is known that there is a relationship between PLKB performance and the performance of leaders at the UPTD KB Hall, Bandar District, Simalungun Regency. It can be concluded that there is a relationship between motivation and the leader's performance which has a very positive effect on PLKB performance. By showing that PLKB performance needs to be improved by being able to adapt to leaders and the work environment in order to get good performance results. So that it is known that there is a relationship between PLKB performance and leadership performance at UPTD KB Hall, Bandar District, Simalungun Regency. It can be concluded that there is a relationship between motivation and the leader's performance which has a very positive effect on PLKB performance. By showing that PLKB performance needs to be improved by being able to adapt to leaders and the work environment in order to get good performance results. So that it is known that there is a relationship between PLKB performance and leadership performance at UPTD KB Hall, Bandar District, Simalungun Regency. It can be concluded that there is a relationship between motivation and the leader's performance which has a very positive effect on PLKB performance. By showing that PLKB performance needs to be improved by being able to adapt to leaders and the work environment in order to get good performance results.